If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(3x + -7)(5x + 3) = 0 Reorder the terms: 2(-7 + 3x)(5x + 3) = 0 Reorder the terms: 2(-7 + 3x)(3 + 5x) = 0 Multiply (-7 + 3x) * (3 + 5x) 2(-7(3 + 5x) + 3x * (3 + 5x)) = 0 2((3 * -7 + 5x * -7) + 3x * (3 + 5x)) = 0 2((-21 + -35x) + 3x * (3 + 5x)) = 0 2(-21 + -35x + (3 * 3x + 5x * 3x)) = 0 2(-21 + -35x + (9x + 15x2)) = 0 Combine like terms: -35x + 9x = -26x 2(-21 + -26x + 15x2) = 0 (-21 * 2 + -26x * 2 + 15x2 * 2) = 0 (-42 + -52x + 30x2) = 0 Solving -42 + -52x + 30x2 = 0 Solving for variable 'x'. Factor out the Greatest Common Factor (GCF), '2'. 2(-21 + -26x + 15x2) = 0 Factor a trinomial. 2((-3 + -5x)(7 + -3x)) = 0 Ignore the factor 2.Subproblem 1
Set the factor '(-3 + -5x)' equal to zero and attempt to solve: Simplifying -3 + -5x = 0 Solving -3 + -5x = 0 Move all terms containing x to the left, all other terms to the right. Add '3' to each side of the equation. -3 + 3 + -5x = 0 + 3 Combine like terms: -3 + 3 = 0 0 + -5x = 0 + 3 -5x = 0 + 3 Combine like terms: 0 + 3 = 3 -5x = 3 Divide each side by '-5'. x = -0.6 Simplifying x = -0.6Subproblem 2
Set the factor '(7 + -3x)' equal to zero and attempt to solve: Simplifying 7 + -3x = 0 Solving 7 + -3x = 0 Move all terms containing x to the left, all other terms to the right. Add '-7' to each side of the equation. 7 + -7 + -3x = 0 + -7 Combine like terms: 7 + -7 = 0 0 + -3x = 0 + -7 -3x = 0 + -7 Combine like terms: 0 + -7 = -7 -3x = -7 Divide each side by '-3'. x = 2.333333333 Simplifying x = 2.333333333Solution
x = {-0.6, 2.333333333}
| AE=500+.7Y | | c=0.12m+8 | | .33(x-6)=3 | | 3b+12=144 | | 4t^2-15t+32=21 | | 3z(9z+6)=27z^2+18z-3 | | 2x+7x-1=0 | | 7(x+2)=23 | | 2(x-1)=4x+2 | | 5(1+2x)-12(x+1)=0 | | y=-7x+19 | | (5x-4)(2x+4)=0 | | 4t^2-15t+32=0 | | 28-3x^2=x^4 | | 10+4a=22 | | 2x+3y=2x+1 | | 7x=-53 | | 4x-5y=3y+4 | | 3(2x+3)=2(x+1)+23 | | 2a-9=a+5 | | 4(x+2)=7(x-9) | | 6x-4(x-16)=46 | | 0.03(2t-9)=0.06(t+2)-0.39 | | (6b-4)(4b-8)= | | x+22=x^2+4x+4 | | A=-4-3a | | y=0.25x+35 | | 3x-8=80-8x | | 7x+2=2x+47 | | 8x+10y=6 | | 2(x+6)-4x=22 | | ln(2x)=0 |